Self-compassion and work engagement among Chinese nurses: exploring mediating effects of depression, anxiety, and stress - Yan Yang; Hongjuan Chang; Shuangxi Guo; Xiao Lei Gao; Lina Wang; Anna Ma (Frontiers Media S.A., 2024)
ObjectiveWork engagement significantly influences both the quality of nursing care and nurses' job performance. In this study, we aimed to explore the mediating effects of negative emotions on the relationship between self-compassion and work engagement among Chinese nurses.MethodA cross-sectional study was performed on nurses in a tertiary A hospital located in Henan province from September, 2023 to December, 2023. Custom-designed digital surveys were disseminated to gather pertinent data. Structural Equation Modelling (SEM) were utilised to analyse the data and determine relationships among self-compassion, negative emotions and work engagement.ResultsA total of 1,201 nurses were included. According to the statistical model, self-compassion (β = 0.116, CI: −0.036 to −0.008, p < 0.001) and negative emotions (β = −0.372, CI: −0.053 to −0.033, p < 0.001) were correlated with work engagement. Furthermore, our analysis revealed that negative emotions partially mediated the relationship between self-compassion and work engagement (β = 0.174, CI: −0.066 to −0.020, p < 0.01).ConclusionThese findings indicate that incorporating self-compassion and negative emotion regulation in interventions targeting work engagement may enhance the overall level of work engagement among nurses, thereby improving job satisfaction and the quality of patient care.